PENGARUH MODEL PEMBELAJARAN SELF-DIRECTED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA UPTD SMP NEGERI 7 GUNUNGSITOLI - Jenni Indah Mitra Ndruru; Ratna Natalia Mendrofa; Yakin Niat Telaumbanua; Netti Kariani Mendrofa (STKIP PGRI Situbondo, 2025)
This research was motivated by a preliminary study conducted at UPTD SMP Negeri 7 Gunungsitoli, which revealed that mathematics learning still employed conventional teaching models and that students' mathematical creative thinking skills were still relatively low. The aim of this study was to determine the effect of the Self-Directed Learning model on students' mathematical creative thinking abilities. The research method used was quantitative with a quasi-experimental approach and a pretest-posttest control group design. The population of the study was all eighth-grade students, with two classes selected through simple random sampling: class VIII-B (23 students) as the experimental group and class VIII-A (24 students) as the control group. The research instrument was an essay test designed to assess students' mathematical creative thinking skills. The results of the one-tailed hypothesis test showed that the calculated t-value was 5.118, which was greater than the t-table value of 1.682. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. Thus, it can be concluded that the Self-Directed Learning model has a significant effect on students' mathematical creative thinking abilities.